ANALYZING THE BEHAVIOURAL PATTERN OF INDIAN RAILWAYS PASSENGERS WITH REGARDS TO DISPOSAL OF WASTE - Gawande, Abhishek (International Journal of Research -GRANTHAALAYAH, 2018)
Indian Railways is the biggest public-sector enterprise in India and connects the entire country. The rail network is spread across the lengths & breadths of the country and one of the biggest worries is the enormous amount of solid waste generated each day by the passengers during the rail journey. It is unfortunate to note that such a huge public transport system does not have a proper waste management system in place. Due to inefficient handling of the waste, there has been a severe impact on the surrounding environment across the rail network. It is in this regards a study was undertaken to enlist the problems related with the disposal of waste during the rail journey and subsequently propose solutions for effective waste management system. The study enumerates the type of waste and the perception of passengers with regards to disposal of waste during rail journey. In order to perform this study, a detailed passenger survey was carried out with the help of structured questionnaire and personal interviews. The survey focused on all kinds of passengers whether travelling by Air conditioned, Sleeper or General class. The data gathered from the study revealed that there are several lacunas in the existing waste management system of Indian Railways. Therefore, a solution of comprehensive waste collection system is proposed primarily in all coaches to ensure proper segregation and disposal of waste, thereby minimizing impacts on surrounding ecosystem. The collected waste can be reused, recycled and thus result in revenue generation for Indian railways. This study could be of great importance to the wider spectrum of researchers, analysts and students for further studies as this area of research has not been studied adequately in the past.